Variation of nitrate concentration and light level on growth rate of diatom Chaetoceros muelleri - Rahayu, Siti Mira; Damar, Ario; Krisanti, Majariana (Acta Aquatica: Aquatic Sciences Journal, 2022)
Microalgae are cultured as natural feed for the cultivation of mollusks, crustaceans (early larval stages), and zooplankton. Diatoms are phytoplankton groups commonly used as feed, one of which is Chaetoceros muelleri. This study aims to identify the optimal nitrate concentrations and light level (irradiance) for the growth rate of C. muelleri. Culture was placed in nitrate 1,330; 5,305; and 27,030 mg/L (N1, N2, N3, respectively); and light 50, 100, and 150 µmol/m2/s, with three replications for each treatment. The response variable observed was the growth rate of C. muelleri and nitrate uptake. Each nitrate treatment resulted in a significant difference in the growth rate of C. muelleri (LSD, p < 0.01). The N3 treatment produced the highest growth rate (average 0,188-0,193 cells/day), while N1 produced the lowest specific growth rate (average 0,149-0,157 /day). In light treatment, a significant difference was only seen in the light levelof 150 µmol/m2/s (LSD, p < 0.05) which produced the highest growth rate (average 0.157-0.193 cells/day), especially in the nitrate N1 and N2. Meanwhile based on the significance test, the interaction between nitrate and light treatment was not significant.Keywords: Chaetoceros muelleri; Growth rate; Irradiance; Nitrate